Allele frequency of a genetic risk variant for necrotizing meningoencephalitis in pug dogs from Europe and association with the clinical phenotype - van Renen, Jana; Kehl, Alexandra; Buhmann, Gesine; Matiasek, Lara A.; Zablotski, Yury; Fischer, Andrea (Frontiers in Veterinary Science, 2024)
Necrotizing meningoencephalitis (NME) in pugs is a potentially fatal disease, which needs lifelong treatment with immunosuppressive or immunomodulatory drugs and shares parallels with acute fulminating multiple sclerosis. Genetic variants of the DLA class II gene are associated with an increased risk for NME. Genetic testing is recommended prior to breeding. The aim of this study was to describe the current allele frequency of a previously identified NME risk variant in the European pug population. A secondary aim was to investigate the association of the NME risk variant with the clinical phenotype in pugs. Results of genetic testing for the CFA12:2605517delC variant in European pugs between 2012 and 2020 were retrieved (n = 5974). A validated questionnaire was mailed to all submitters of samples for further information on neurological signs, diagnostic tests, and disease course. The allele frequency of the CFA12 NME risk variant was 25.7% in the European pug population dogs; 7.4% of the dogs were homozygous and 36.7% were heterozygous for the NME risk variant on CFA12. Completed questionnaires were available in 203 dogs including 25 dogs with epileptic seizures or other neurological signs. The clinical phenotype was consistent with NME in 3.9% with a median age of onset of 1.0 years, and indicative of idiopathic epilepsy in 2.9% with a median onset of 2.5 years. 11 dogs remained unclassified. Pugs with the NME phenotype were significantly more frequently homozygous for the NME risk variant on CFA12 compared to pugs ≥6 years without neurological signs or seizures (p = 0.008). The CFA12:2605517delC genetic risk variant is widely distributed in the European pug population and frequently homozygous in pugs with an NME phenotype. The data support the clinical relevance of the CFA12:2605517delC genetic risk variant.